A study on customers perception towards service quality provided by Sabah Ports Sdn Bhd / Jodie Kessy Primus - Primus, Jodie Kessy (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2008)
A good perception towards the service quality by customers is essential for all business or organizations. This study is conducted to know customers' perceptions and degree of satisfaction towards the service quality provided by Sabah Ports Sdn. Bhd (SPSB) in Kota Kinabalu district. The Ports are namely Kota Kinabalu Port, Sepangar Container Port and Sapangar Bay Oil Terminal. Besides, this study also recommends to improve the service quality at Kota Kinabalu district Ports. Techniques that are used for this research regarding to obtain information from customers who are among the forwarding agents as the respondents are through questionnaire distribution and self-observation. Through the questionnaire distribution, data will be collected which then will be processed with the use of Statistical Package for Social Science or SPSS. Information obtained through this process then will be converted into charts and tables in the final process for evaluation to be done. Based on the research conducted, majority of the customers at Kota Kinabalu district ports gave good and positive responses and feedback .Towards the end of this study, the respondents' suggestions can be used by SPSB to improve their service quality in the future.